ANALISIS PENGELOLAAN ZAKAT PRODUKTIF DAN PENYALURAN DANA ZAKAT UNTUK PEMBERDAYAAN EKONOMI MUSTAHIK DI BAZNAS PROVINSI BENGKULU - Rezka Anastasha; Amir Mukadar; Dharma Setiawan (UM. Bengkulu, 2025)
This article aims to determine the implementation of the Zakat Maal Distribution System Analysis at the National Zakat Agency of Bengkulu City (BAZNAS). The analysis aims to determine whether the zakat mal distribution system implemented complies with Islamic sharia principles and government regulations. This study used field research, also known as empirical research. Data were obtained through direct interviews with BAZNAS employees in Bengkulu City and several zakat recipients. The results of this study conclude that the distribution has been running quite well and is in accordance with Islamic principles and applicable laws and regulations in Indonesia. The National Zakat Agency (BAZNAS) of Bengkulu City has distributed zakat funds to various groups categorized as mustahik (zakat recipients), such as the poor, those in need, converts to Islam, and others. The utilization of zakat funds covers various areas, including educational assistance, business assistance, social assistance, and healthcare. Zakat distribution has been successful, but low public awareness remains, leading to uneven distribution, with monitoring and evaluation to ensure zakat programs reach their intended targets.